The Influence of Consumer Product Knowledge, Trust, and Risk Perception on Purchase Intention Among Shopee Consumers: The Role of Reviews as a Moderating Variable - Suri, Dian Mei; Atika, Atika; Aisyah, Siti (Graduate Program Magister Manajemen Pendidikan, 2024)
The development of e-commerce has changed consumer behavior. With the presence of e-commerce, many habits have changed, starting from previous shopping habits in offline stores, now switching to shopping at online stores using shopping sites and applications such as Shopee, because it makes it easier for consumers to make buying and selling transactions online. However, Shopee, which is a consumer favorite, has several problems, including some consumers who buy products at Shopee feeling disappointed because the goods purchased do not match expectations, thus affecting consumer buying intentions. Several previous studies have shown that there is a relationship between consumer trust and purchasing decisions. This study uses descriptive quantitative research using multiple linear regression analysis. The subjects of this research are Shopee consumers. The variables used in this study are consumer product knowledge, trust, risk perception and reviews as moderating variables. The results of the research show that consumer product knowledge has a positive but not significant effect on Shopee consumers’ purchasing decisions. Meanwhile, the variables of trust, risk perception and reviews have a significant positive effect on Shopee consumers’ purchase intentions. Then the review variable is not able to moderate the relationship between consumer product knowledge and purchase intention. However, reviews are able to moderate the relationship between trust, risk perception and purchase intention.